Case report: Application of targeted NGS for the detection of non-canonical driver variants in MPN - Zhang, Jin; Shen, Kefeng; Xiao, Min; Huang, Jinjin; Wang, Jin; Wang, Yaqin; Hong, Zhenya (Frontiers in Genetics, 2023)
Background: JAK2, CALR, and MPL gene mutations are recognized as driver mutations of myeloproliferative neoplasms (MPNs). MPNs without these mutations are called triple-negative (TN) MPNs. Recently, novel mutation loci were continuously discovered using next-generation sequencing (NGS), along with continued discussion and modification of the traditional TN MPN. Case presentation: Novel pathogenic mutations were discovered by targeted NGS in 4 patients who were diagnosed as JAK2 unmutated polycythaemia vera (PV) or TN MPN. Cases 1, 2, and 3 were of patients with PV, essential thrombocythemia (ET), and primary myelofibrosis (PMF); NGS detected JAK2 p.H538_K539delinsQL (uncommon), CALR p.E380Rfs*51 (novel), and MPL p.W515_Q516del (novel) mutations. Case 4 involved a patient with PMF; JAK2, CALR, or MPL mutations were not detected by qPCR or NGS, but a novel mutation SH2B3 p.S337Ffs*3, which is associated with the JAK/STAT signal transduction pathway, was found by NGS. Conclusion: NGS, a more multidimensional and comprehensive gene mutation detection, is required for patients suspected of having MPN to detect non-canonical driver variants and avoid the misdiagnosis of TN MPN. SH2B3 p.S337Ffs*3 can drive MPN occurrence, and SH2B3 mutation may also be a driver mutation of MPN.